Implementation of self-care symptom management program to enhance the quality of life of cancer patients undergoing chemotherapy and their family caregivers - Haryani, Haryani; Rachmat, Kuniarti; Suseno, Probo; Effendy, Christantie (International Journal of Research in Medical Sciences, 2017)
Background: Chemotherapy affects the condition of cancer patients, physically, psychologically, socially and spiritually. The Self-care Symptom Management (SSM) program is a psychoeducation program with the goal of enhancing patients’ self-care abilities to manage the side effects of chemotherapy, and thus improve the Quality of Life (QOL) of adult cancer patients and their family caregivers. The objective of the study is to determine the effects of the SSM program on the QOL of cancer patients undergoing chemotherapy and their family caregivers. Methods: The study adopts a quasi-experimental design, with one group and pre- and post-intervention tests. The study was conducted in a public hospital in Yogyakarta, Indonesia, with 40 cancer patients and 30 of their family caregivers. The QOL of patients is measured using the EORTC QLQ-C30, and for their family caregivers the CQOLC is used. Data analysis are carried out using a paired t-test and Wilcoxon test, with a 95% level of significance. Results: The data show significant differences between the mean scores on a single item of sleep disturbance (15.84 points) and a single item of financial difficulties (8.34 points) before and after the implementation of the SSM program. Clinical relevance is shown on a single item of sleep disturbance (≥10 points). Conclusions:The Self-care Symptom Management program represents a promising intervention to promote self-care management for cancer care in Indonesia.